O diálogo colaborativo como facilitador da aprendizagem dos alunos de nível básico de inglês como língua estrangeira - Lacerda, Aline Goneli de (2009)
Researches in L2 acquisition have acknowledged the importance of collaborative dialogue in pairs as a facilitator for the learning of EFL by advanced students. However, there are few evidences whether these benefits would apply in the same way to students with a basic knowledge of the FL. Grounded in the Comprehensible Output Hypothesis (Swain, 1985), the present study sought to investigate the role of collaborative dialogue in the enhancement of low-level learners written production, especially in relation to the use of connectives and verbs in the Simple Past tense in English. The research participants were six students from a public school. The methodology employed was based on tasks involving the production and reformulation of narratives in English. The data analysis focused on the collaborative dialogues in terms of Language Related Episodes (LREs). The appreciation of the verbal protocols and the texts produced provided evidences about the strategies used by the students, during the completion of the tasks, and the decisions made by them in relation to the form of the FL. The results corroborate the Comprehensible Output Hypothesis. The data revealed the occurrence of the three aspects that promote discourse reformulation in the students collaborative dialogues the perception of the gaps between the FL and their IL, hypothesis formulation and the reflection about language through language. It was concluded that, depending on the individuals and the circumstances, the negotiations established through collaborative dialogue may facilitate FL learning.